Iron‐load exacerbates the severity of atherosclerosis via inducing inflammation and enhancing the glycolysis in macrophages. Issue 10 (29th March 2019) - Hu, Xiaorong; Cai, Xinyong; Ma, Ruisong; Fu, Wenwen; Zhang, Changjiang; Du, Xianjin
Abstract: Atherosclerosis is still the major cause of morbidity and mortality all over the world. Recently, it has been reported increased levels of tissue iron increase the risk of atherosclerosis. However, the detailed mechanism of iron‐induced atherosclerosis progression is barely known. Here, we used apoE‐deficient mice models to investigate the effects of low iron diet (<0 mg iron carbonyl/kg), high iron diet (25, 000 mg iron carbonyl/kg) on atherosclerosis in vivo. As exhibited, we observed that CD68 was significant enriched by high iron diet in apoE‐deficient mice. In addition, transforming growth factor β, tumor necrosis factor α, interleukin 6 (IL‐6), IL‐23, IL‐10, and IL‐1β levels were also greatly induced by high iron diet. Then, we found that the iron load promoted the inflammation response in macrophages. Moreover, macrophage polarization is a process by which macrophage can express various functional programs in activating macrophages. Here, we observed that iron‐load macrophages were polarized toward a proinflammatory macrophage phenotype. The polarization of M1 macrophage was promoted by ferric ammonium citrate (FAC) in bone marrow derived macrophages (BMDMs). Furthermore, ECAR and cellular OCR in BMDM with or without FAC was examined. As shown, BMDM indicated with 50 μM FAC showed a significant increase in basic state and maximal ECAR in contrast to the control group. However, there was no significant difference in OCR. This indicated that the glycolysis was involved in the polarization of M1 macrophage triggered by iron‐load. In conclusion, we indicated that the iron load exacerbates the progression of atherosclerosis via inducing inflammation and enhancing glycolysis in macrophages. Abstract : We found that iron load could promote the severity of atherosclerosis and the inflammation responses in macrophages. Meanwhile, the polarization of M1 macrophages was induced by iron by enhancing the glycolysis. We indicated that iron load exacerbated the progression of atherosclerosis via inducing inflammation and glycolysis in macrophages.